2020
DOI: 10.1002/cjce.23828
|View full text |Cite
|
Sign up to set email alerts
|

CO2 conversion through combined steam and CO2 reforming of methane reactions over Ni and Co catalysts

Abstract: Ni-Co bimetallic and Ni or Co monometallic catalysts prepared for CO 2 reforming of methane were tested with the stimulated biogas containing steam, CO 2 , CH 4 , H 2 , and CO. A mix of the prepared CO 2 reforming catalyst and a commercial steam reforming catalyst was used in hopes of maximizing the CO 2 conversion. Both CO 2 reforming and steam reforming of CH 4 occurred over the prepared Ni-Co bimetallic and Ni or Co monometallic catalysts when the feed contained steam. However, CO 2 reforming did not occur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…On the one hand, the loss of active area of Ni particles was evidenced by the increase of the crystallite size and became twice as the corresponding value of the reduced sample (Tab. 1), owing to the exposure to the H 2 O stream as it was also observed for Ni/Ce catalysts [32]. On the other hand, the decrease in the catalytic activity of the sample was also due to a quick coke formation on the surface of the solid as it was indicated by the results of the thermodynamic calculus and clearly observed by the Raman spectra presented in Fig.…”
Section: Activity Performance Evaluationsupporting
confidence: 62%
“…On the one hand, the loss of active area of Ni particles was evidenced by the increase of the crystallite size and became twice as the corresponding value of the reduced sample (Tab. 1), owing to the exposure to the H 2 O stream as it was also observed for Ni/Ce catalysts [32]. On the other hand, the decrease in the catalytic activity of the sample was also due to a quick coke formation on the surface of the solid as it was indicated by the results of the thermodynamic calculus and clearly observed by the Raman spectra presented in Fig.…”
Section: Activity Performance Evaluationsupporting
confidence: 62%
“…Garcia et al [56] studied the effect of 0.04% Rh2O3 and found the enhanced CDSRM performance. Furthermore, Shakouri et al [57] studied the effect of Ni-Co bimetallic catalyst and compared its performance with monometallic Co and Ni catalyst. Authors concluded that Ni-Co bimetallic exhibits better performance than the monometallic ones as it converts 70% more CO2 and the respective H2/CO ratio was 1.8-2.…”
Section: Ni-based Catalysts For Cdsrm Reactionmentioning
confidence: 99%
“…The magenta cluster, which bridges the blue and red clusters, concentrates on iron (Fe), metals, complexes, Mn, S, and K-edge. [25] and the other with LiFePO 4 and batteries (red cluster) entitled 'Chemical Speciation and Mapping of the Si in Si Doped LFP Ingot with Synchrotron Radiation Technique'. [26,27] Nature published the most cited article since 2018 entitled 'Reversible Mn 2þ =Mn 4þ Double Redox in Lithium-Excess Cathode Materials'.…”
Section: Applicationsmentioning
confidence: 99%